Boosting EFL Speaking Skills Through Think Pair Share Strategy in The Digital Era: Integrating the Reallife App for Eleventh Grade Students - Nabila Humaira; Francisca Maria Ivone; Nanang Zubaidi (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
In an era where English proficiency opens global doors, speaking fluency remains the Achilles' heel for many language learners. Initial observations at a senior high school in Kota Malang Grade XI students struggled with speaking, lacked confidence, and had low motivation to improve their speaking ability. Teachers also faced constraints in applying effective speaking strategies due to limited instructional time. To address these issues, this study integrated the Think-Pair-Share (TPS) strategy with the RealLife English application, focusing on the “Pair” phase to maximize interaction and authentic communication. This Classroom Action Research (CAR), following Kemmis & McTaggart’s model, involved 36 eleventh-grade students over eight meetings. Data were collected through speaking tests, questionnaires, classroom observations, and interviews. Students’ speaking performance was assessed using an analytical scoring rubric covering fluency, lexical resource, grammar, and pronunciation. Findings indicate a significant improvement in speaking fluency, supported by notable gains in other criteria. Students reported enhanced vocabulary, greater confidence, and deeper cultural awareness through interactions with international peers on RealLife. Analysis of perceptions revealed three key outcomes: meaningful learning through cultural exchange, effective synergy between a classical cooperative strategy and digital tools, and improved learning efficiency when integrating flipped learning with TPS. This research demonstrates that TPS combined with RealLife offers a powerful, innovative approach to fostering speaking proficiency in EFL contexts. However, there are some shortcomings that should be noted, including the connection issue during the action phase. Some suggestion is also taken into this study.